Workshop Report on National ICT4Ag+ Indonesia - Jardinero, Benedict; Selasa Pagianti, Tri; Putri, Devanda; Tresnawati, Tika (International Rice Research Institute, 2023)
The National ICT4Ag+ Event in Indonesia is a complementary activity to the global ICTforAg 2023 scheduled on November 7-9, 2023. It provided an inclusive opportunity for local participants to engage with their peers in the vibrant local digital ecosystem and connect with the global community. The CGIAR Research Initiative on Digital Innovation, the International Rice Research Institute (IRRI) and the Badan Standardisasi Instrumen Pertanian (BSIP) of Indonesia co-organized the National ICT4Ag Event on 9 October 2023 at the BSIP Headquaters in Jakarta.